Employees’ perception of management skills in the Los Olivos Municipal Hospital - Arrascue Lino, Irma Emperatriz (2021)
Objective: Analyze management skills from employees’ perception in the Los Olivos Municipal Hospital in 2019. Methods: Quantitative, correlational, cross-sectional study. A simple random sample of 52 participants was applied. We used a questionnaire to assess perceptions regarding management skills, consisting of 27 questions and 4 dimensions, with a Cronbach’s alpha reliability value of 0.97. We used Pearson’s chi-squared test to analyze correlation between management skills variable and sociodemographic variables. Results: Management skills were considered adequate in analytic and interpersonal dimensions by 69% of participants, while emotional and motivational skills and values were considered regular by 69% and 58%, respectively. 55.8% of participants perceived their bosses’ management skills as adequate, 44.2% perceived them as regular, and none as inadequate. The only sociodemographic variable that was associated with management skills was service time. Conclusion: 55.8% of the health personnel in the Los Olivos Municipal Hospital perceived management skills as adequate.